Процес формування структурних підрозділів Чернігівського державного педагогічного інституту (1954 – 1998 рр.) - Боровик, М. (Сiверянський лiтопис, 2015)
Увазі читача пропонуються маловідомі сторінки історії Чернігівського педагогічного
інституту. Мова йде про зміни, які відбулись у структурі факультетів та кафедр за
майже 44-річну його діяльність. Вниманию читателя предлагаются малоизвестные страницы истории Черниговского педагогического института. Речь идет об изменениях в структуре факультетов
и кафедр за почти 44-летнюю его деятельность. A few reorganizations took place in the Chernihiv National Pedagogical Institute called in
the name of T.H. Shevchenko, which has its rich history that lasts for almost 100 years. It was
founded as an institute for teachers, then it was a pedagogical one for a short period of time.
After that it was renamed to the institute of folk education and the institute of social education.
Only in December 1954 the institute becomes a pedagogical one. During its existence many
changes took place in its structural subdivisions, while new faculties appeared. However, this
issue is not researched enough in any source of historical literature. That is why the purpose
of this article is to research the process of forming the structure of the faculties of Chernihiv
Pedagogical Institute from the very beginning.